2021
DOI: 10.1007/s43188-020-00085-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of organochlorine pesticides residues in fish from Edko Lake (North of Egypt) using eco-friendly method and their health implications for humans

Abstract: Levels of organochlorine pesticides (OCPs) residues in tilapia fish and their health risk associated with the consumption of fish from Edko lake, Egypt were determined. The quick, easy, cheap, effective, rugged, and safe method (QuEChERS) was used for extraction and clean-up of 18 OCPs residues from fish followed by GC-ECD and GC-ITD analytical tools were employed for identification of OPs. Out of the 18 OCPs, only heptachlorepoxide, p,p-DDE, dieldrin, p,p-DDD, and endrin ketone were detected in muscles of fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
4
5
1
Order By: Relevance
“…This minimum exposure with no public health risk (HRI < 1) was recorded in different studies, for instance in Ghana by Gbeddy et al ( 2012 ) and Akoto et al ( 2016 ). Similar to our finding, HRI of Endosalfan I, Endosalfan II, 4, 4, DDE, and 4, 4, DDD residues in fish of Edko Lake, Egypt did not have a public health risk (HRI < 1) (Abbassy et al, 2021 ). Another study by Hasan et al ( 2022 ) in Bangladesh detects less than 1 HRI organochlorine pesticide in fish.…”
Section: Results and Discusionsupporting
confidence: 91%
See 1 more Smart Citation
“…This minimum exposure with no public health risk (HRI < 1) was recorded in different studies, for instance in Ghana by Gbeddy et al ( 2012 ) and Akoto et al ( 2016 ). Similar to our finding, HRI of Endosalfan I, Endosalfan II, 4, 4, DDE, and 4, 4, DDD residues in fish of Edko Lake, Egypt did not have a public health risk (HRI < 1) (Abbassy et al, 2021 ). Another study by Hasan et al ( 2022 ) in Bangladesh detects less than 1 HRI organochlorine pesticide in fish.…”
Section: Results and Discusionsupporting
confidence: 91%
“…This minimum exposure with no public health risk (HRI < 1) was recorded in different studies, for instance in Ghana byGbeddy et al (2012) andAkoto et al (2016). Similar to our finding, HRI of Endosalfan I, Endosalfan II, 4, 4, DDE, and 4, 4, DDD residues in fish of Edko Lake, Egypt did not have a public health risk (HRI < 1)(Abbassy et al, 2021).Another study byHasan et al (2022) in Bangladesh detects less than 1 HRI organochlorine pesticide in fish. In contrast to our finding, the study done byYohannes et al (2014) on a Rift Valley Lake-Lake in Ziway, Ethiopia, indicated a potential cancer risk from consumption of the fish from the calculated hazard ratio (HR).…”
supporting
confidence: 92%
“…High sensitivity, high resolution, and symmetrical peak morphologies (no tailing) can be achieved by optimizing the chromatographic settings across a number of trials for the separation and detection of OCPs [ 355 ]. The method should be kept under regular evaluation and updated as necessary to reflect advancements in technology, legislation, or lab specifications.…”
Section: Results and Discussion: Literature Reviewmentioning
confidence: 99%
“…It is worth noting that the highest organochlorine and organophosphorus compounds have been detected in Nile tilapia in autumn (106.8 ppb), followed by winter (45.63 ppb), then summer (40.9 ppb) and spring (33 ppb), respectively. This might be as a result of the high hydrophobicity and lipophilicity of these compounds as well as their potential retention in organisms' organic phases 32 .…”
Section: Resultsmentioning
confidence: 99%